2014
DOI: 10.1057/ejdr.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Child Labor in Africa and Asia: Household and Context Determinants of Hours Worked in Paid Labor by Young Children in 16 Low-Income Countries

Abstract: We study the number of hours children in Africa and Asia are involved in paid child labor on the basis of a newly developed database with information on 168,000 children living in 16 countries.The proportion of involved children varies between 1 and 8 percent, with generally lower figures in Asia. Children work on average 13 hours in Africa and 30-38 hours in Asia. Multilevel analysis shows the variation in child labor to be almost completely related to household level factors, with wealth and parental educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…They do not use models but a weighted count. Webbink et al (2015) provide a Tobit model of working hours in paid work but do not critically differentiate child labour from child work. Giri and Singh (2016) attempt to count child labourers in India by integrating economic activities and domestic chores and including 'nowhere children' 4 ; they do not make use of models but multiply the ratio of child labourers by the population.…”
Section: Differentiation Separating Child Labour From Child Workmentioning
confidence: 99%
“…They do not use models but a weighted count. Webbink et al (2015) provide a Tobit model of working hours in paid work but do not critically differentiate child labour from child work. Giri and Singh (2016) attempt to count child labourers in India by integrating economic activities and domestic chores and including 'nowhere children' 4 ; they do not make use of models but multiply the ratio of child labourers by the population.…”
Section: Differentiation Separating Child Labour From Child Workmentioning
confidence: 99%
“…Emerson and Souza (2011) explored whether working as a child labourer is harmful to individual’s adult earnings and found that paid child labour is associated with lower adult earnings partly because of the inability of child labourer to attain a high level of education. Webbink et al (2015) drew attention to the number of hours a child engaged in paid labour and found that poverty and other household-level factors mainly affect the variation in the hours of paid child labour. Emerson and Souza (2003) examined whether there is the intergenerational persistence of paid child labour empirically and found that children are more likely to be child labourers if their parents are and less likely to be paid child labourers if their parents are well educated, suggesting that paid child labour might produce the chain of poverty over generations.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Previous studies on paid child labour (e.g. Webbink et al , 2015) did not assume parental migration explicitly as another possible measure of poverty reduction. Similarly, those on parental migration (e.g.…”
Section: Research Gapmentioning
confidence: 99%
“…There have been several studies on child labor. Webbink et al (2015) studied the number of hours children in Africa and Asia were involved in paid child labor from data on 169,000 children living in 16 countries. They found variations in children's work hours to get wages, mainly due to household-level factors with poverty still a major driving factor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research on child labor has commonly utilized micro-data at the household level (Tang et al, 2018;Menon & Rodgers, 2018;Posso, 2017;Webbink et al, 2015;Ali & Arabsheibani, 2017). To the best of our knowledge, none of the previous studies has used macro-data for the case of Indonesia.…”
Section: Introductionmentioning
confidence: 99%